ANALISIS KESULITAN BELAJAR MATEMATIKA MATERI BANGUN DATAR SISWA KELAS IV UPT SDN 017 MAYANG PONGKAI KABUPATEN KAMPAR - Luciya Anenshie; Siti Quratul Ain (STKIP Subang, 2023)
Learning difficulties are conditions of students who face difficulties and inability of students in learning by examining the background, the form of symptoms and causes of difficulties. The aims of this research are 1). to analyze the form of learning difficulties in mathematics on flat material in class IV 2). To analyze the factors that cause learning difficulties in mathematics on flat shapes in class IV. This research method is descriptive qualitative with data collection techniques of interviews, documentation and assisted math tests. Data analysis used according to Milles and Huberman. The results of this study are that there are 4 forms of student learning difficulties, namely, 1) Students have difficulty understanding the concept of flat shapes, 2) Students have difficulty relating to the practical principles of flat material, 3) Students have difficulty dealing with symbols, namely the formula area and circumference of flat shapes, 4) Students have difficulty understanding the language of mathematics, namely understanding the shape of the story. Factors causing these difficulties are influenced by 2 factors, namely internal and external. Internally, namely the attitude of students learning students who are lazy when studying and student learning motivation is low so that students are less enthusiastic and less curious. Externally, namely, 1) Teachers with monotonous methods and unattractive media, 2) the environment is clean and comfortable but the classrooms lack maintenance, 3) facilities and infrastructure, namely facilities that are less supportive such as lack of learning books and projectors, while infrastructure is a lack of practicum buildings, 4) family environment, namely students lack guidance at home due to family economic conditions.